Fishery biology research: glimpses on practices and application for genetic resource conservation - DEVARAJ, M (The Indian Journal of Animal Sciences, 2010)
India is bestowed with rich natural resources in which the freshwater, coastal and marine living resources are of prime importance in view of the total dependence of the humanity on these resources for its well-being. Sustained anthropogenic activities such as fishing, coastal industries, shipping and ports, ship breaking, dredging, agriculture and land based industries have profound impacts on these resources ranging from least serious to most serious in nature prompting appropriate regulatory and conservation measures. Voluminous research findings on the biology of these living organisms are extensively useful for the formulation and implementation of the regulatory measures of conservation. An estimated 650 million fish eating people out of the total population of 1,300 million require 7.2 million tons at the rate of 11kg/year/head. Out of 24,618 species about 2500 occur in Indian waters in which 1570 are marine and nearly 200 species are of commercial importance. Almost all the species exhibit faster growth rate and attain maturity within a year, have a high fecundity, more than one spawning in a year. South-west and north-east monsoons have a profound influence on these resources. Single species dominance is noticed in pelagic resources and due to continued exploitation pelagic resource emerges as a dominant one in recent times. Most of the species studied are exposed to higher fishing pressure with symptoms and indications of over-fishing and as such the marine fisheries suffer due to inappropriate exploitation, over-dependence on trawling, target fishing, habitat degradation and resource degradation. An extensive study on various aspects of biology of different resource has lead to formulation of various Act and Rules on fishery regulation on limited entry, temporal restriction, spatial restriction, gear restriction, mesh size regulation and fishing holidays. Determination of spawning season helps fixing the months of fishing ban.Determination of fecundity and number of spawners helps finding out biomass spawning stock biomass and spawnerrecruitment relationship. This, in turn, is helpful to regulate fishing effort. The estimates on growth, (based on length frequency or on otoliths) is used to further estimate the mortality and stock biomass, which are necessary to understand the status of exploitation, and further to regulate fishing effort and to fix catch quotas. Analysis of length-weight relationship, gonadosomatic index and Kn values are useful to understand the well-being of the fish. Studies on food and feeding habits are used to understand the tropho-dynamics and energy flow in an ecosystem, which are recently used for trophic modeling and for ecosystem-based fisheries management. Estimation of length-at-maturity is used to find out whether the fish are allowed to spawn at least once in their life and to recommend Minimum Legal Size. Estimation of juveniles in the exploited populations is used to suggest optimum mesh size of fishing gear. Collection of continuous data on species composition in the landings is helpful to identify the species, whose contribution decreased once the time period is over, and to take appropriate measures to conserve the species. Shrimp larval biology studies lead into commercial shrimp hatchery. Carp biology, induced breeding techniques, studies on shrimp biology and feeding lead into successful carp and shrimp farming and development of feeds. Studies on ornamental fish breeding biology lead into ornamental fish hatchery of the clownfish etc. Studies on fish behaviour and aggregation lead into development of artificial reefs & FADS. Biological characteristics studies have resulted in recommendations for conservation of whales, dolphins and porpoise. Biodiversity studies have helped to understand the vulnerability of coral reefs and to develop plans for restoration of coral reefs. Biological studies on reservoir fisheries lead into stocking of fingerlings in reservoirs and harvesting fish catch. Remote sensing has helped to locate the Potential Fishing Zones (PFZ) pertaining to mostly pelagic fishery resources. Sea ranching has helped the artificial propagation of seeds of different depleted species in the natural environment. Artificial reefs enhance the livelihood and socio-economic condition of the coastal fisher-folk as they not only enrich the biological components of the area concerned but also congregate the fish population leading to the improvement in the quality and quantity of the living resources of the area. Prevention of trawl operation in shallow waters will develop the area into nursery grounds for different fishery resources. Many more technological interventions are Mussel culture, Edible Oyster culture, Pearl Oyster culture, Finfish culture and Seaweed culture. Further continued research in different aspects of biology, environment and climate change is essential for proper conservation of the natural resources.